INTERCULTURAL COMMUNICATIVE COMPETENCE DEVELOPMENT IN JOURNALISM STUDENTS - Natalia Mykytenko; Marta Fedorchuk; Olena Ivasyuta; Nataly Hrynya; Andriy Kotlovskyi (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2022)
The paper is focused on the intercultural communicative competence as an integral part of vocational training of journalism students. The aim of the paper is: 1) to define the intercultural communicative competence dimensions; 2) to outline the ways of development of intercultural communicative competence of journalism students; 3) to find out the attitudes of journalism students to intercultural communicative competence development; 4) to assess the levels of journalism students' intercultural communicative competence and develop recommendations for its development. A mixed research design was employed which involved 14 ESP teachers and 26 bachelor students of Ivan Franko National University of Lviv during the autumn trimester of 2021. The study shows that the students are fully aware of the necessity to develop intercultural communicative competence. Based on the survey of the ESP teachers, we outlined the dimensions of journalism students' intercultural communicative competence development and suggested the ways of building intercultural communicative competence in journalism students. The levels of assessment of intercultural communicative competence of journalism students were outlined and defined. The final results indicate that journalism students whose study was more practice than theory oriented (group 1) showed better learning outcomes than those who were mostly focused on the acquisition of theoretical knowledge (group 2). Methodical guidelines for ESP teachers were developed.